HOW MATHEMATICS IS TAUGHT IN INCLUSIVE CLASSROOMS: A SYSTEMATIC LITERATURE REVIEW - FUJIAMA MARJUD (LPPM Universitas Banda Naira, 2026)
This research examines teaching mathematics in inclusive classrooms through the PRISMA method with a focus on approaches, strategies, and challenges in creating inclusive learning. Inclusive education aims to integrate students with various needs, including students with special needs, into regular classes. Strategies used include collaborative teaching, curriculum adaptation, differentiation of learning, and utilization of interactive technologies such as Geogebra and Microsoft PowerPoint, which effectively explain abstract mathematical concepts concretely. Collaboration between teachers, parents, and the community is also a key element. However, various challenges include limited training teachers, lack of resources, and discrimination that can hinder student participation. Overcoming this requires continuous training for teachers in implementing inclusive strategies and assistive technology, education policy reforms that encourage greater collaboration, and individual ability-based evaluation for fairer assessment. This research emphasizes the importance of a systemic approach in overcoming social and economic barriers in inclusive education. By creating adaptive learning environments, teaching mathematics in inclusive classrooms can increase student engagement, create equity and support success regardless of background or special needs. These strategies can build effective and sustainable inclusive education, strengthening the foundation of equity in the education system.